Medicinal plants of northern Angola and their anti-inflammatory properties. (24th April 2018) - Pompermaier, Luca; Marzocco, Stefania; Adesso, Simona; Monizi, Mawunu; Schwaiger, Stefan; Neinhuis, Christoph; Stuppner, Hermann; Lautenschläger, Thea
Abstract: Ethnopharmacological relevance: 32 plants, from which 30 are used in local traditional medicine – identified by interviews with the resident population – in the province of Uíge in northern Angola for the treatment of inflammation related disorders, were screened on different anti-inflammatory parameters. Three extracts were selected for a detailed ethnobotanical, pharmacological and phytochemical investigation based on their in vitro activity. Aim of the study: We aimed to assess the in vitro anti-inflammatory activity of these plants and highlight the active principles of the three most promising candidates. Materials and methods: Plant material was collected in northern Angola during eight field trips from 2013 to 2015 based on data documented in 61 interviews with 142 local informants. 36 methanol (MeOH) extracts were prepared and tested at different concentrations (100, 50, 10 µg/mL) to evaluate their inhibition on cyclooxygenase (COX)−2 expression and on nitric oxide (NO) release in lipopolysaccharide (LPS)-stimulated J774A.1 macrophages. Five selected extracts were additionally tested at the lower concentrations of 5, 2.5, and 1.25 µg/mL and for their potential on inhibition of tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6) release. The major compounds of three of those five extracts were either identified by HPLC coupled with (tandem) mass spectrometry and comparison with data from literature or isolated from the respective extracts and confirmed by NMR experiments (one and two dimensional). Results: 30 plant species with in total 161 citations were mentioned by the informants to have anti-inflammatory properties. The predominantly used plant part is the leaf (39%), followed by underground organs like roots and rhizomes (25%), bark (18%) as well as fruits and seeds with 15%. With 47%, decoction is the most frequent preparation form. A large number of the MeOH extracts showed promising activities in our preliminary screening for the inhibition of COX-2 expression and NO release. Five extracts with high activities in both assays showed also concentration dependent inhibition at lower concentrations and a decreased release of two additional pro-inflammatory mediators (IL-6 and TNF-α) vs. LPS. Three leaf extracts where chosen for a detailed investigation, which lead to the identification of several constituents: verbascoside and isoverbascoside ( Acanthus montanus ), geraniin, chebulagic acid and a large flavonoid fraction ( Alchornea cordifolia ) as well as the four flavonoids astilbin, isovitexin, isoorientin and swertisin ( Chaetocarpus africanus ). Their implication in the observed biological activity was proved by comparison with published data of these compounds in identical or similar pharmacological models. Conclusions: The indigenous use of these plants against inflammation related ailments could be – at least partly – verified by our in vitro models for many of the investigated extracts. Acanthus montanus and Alchornea cordifolia particularly stood out with their high activity in all four performed assays, which was in accordance with pharmacological studies of their major constituents in literature. In addition, this study was the first phytochemical investigation of Chaetocarpus africanus and first description of the occurrence of the ellagitannins geraniin and chebulagic acid in Alchornea cordifolia . These results support the traditional use and should encourage further investigations of medicinal plants of northern Angola. Graphical abstract: